2017
DOI: 10.3389/fmicb.2017.01756
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial, Archaeal, and Eukaryotic Diversity across Distinct Microhabitats in an Acid Mine Drainage

Abstract: Acid mine drainages are characterized by their low pH and the presence of dissolved toxic metallic species. Microorganisms survive in different microhabitats within the ecosystem, namely water, sediments, and biofilms. In this report, we surveyed the microbial diversity within all domains of life in the different microhabitats at Los Rueldos abandoned mercury underground mine (NW Spain), and predicted bacterial function based on community composition. Sediment samples contained higher proportions of soil bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 87 publications
1
54
0
2
Order By: Relevance
“…Members from this group have been previously detected in the sediments of other AMD habitats like Rio Tinto (Sánchez-Andrea et al . 2011) or Los Rueldos mercury underground mine in Spain (Mesa et al . 2017), and it has been suggested that they could have an important role in the oxidation of iron and sulfur compounds (Mesa et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Members from this group have been previously detected in the sediments of other AMD habitats like Rio Tinto (Sánchez-Andrea et al . 2011) or Los Rueldos mercury underground mine in Spain (Mesa et al . 2017), and it has been suggested that they could have an important role in the oxidation of iron and sulfur compounds (Mesa et al .…”
Section: Resultsmentioning
confidence: 99%
“…2011) or Los Rueldos mercury underground mine in Spain (Mesa et al . 2017), and it has been suggested that they could have an important role in the oxidation of iron and sulfur compounds (Mesa et al . 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we presented MAGs from four such phyla -the Dormibacterota, the Elusimicrobiota, the Eremiobacterota, and the Patescibacteria. Elusimicrobiota have also been found in AMD environments across the globe including in Spain (70,72), France (29), and Svalbard (73), but it is not abundant in these environments. The only cultivated taxa from this phylum are strictly anaerobic (74)(75)(76).…”
Section: Phylogenetic Relatedness and Metabolismmentioning
confidence: 99%
“…Currently, most photoferrotrophic isolates have originated from either freshwater sediment and lakes or marine sediments (Bryce et al 2018). The occurrence of Chlorobi has been reported in 16S rRNA gene sequencing surveys of acid mine drainage (Volant et al 2014;Mesa et al 2017) and soils impacted by circumneutral mine drainage (Pereira, Vicentini and Ottoboni 2014) though at low abundance (<1%). It is possible that the high relative abundance for Chlorobi-affiliated OTUs at Ynysarwed represents a previously overlooked microbial metabolism in circumneutral mine drainage that can greatly impact pollutant turnover.…”
Section: Ecological Successionmentioning
confidence: 99%